2013
DOI: 10.1111/jeb.12273
|View full text |Cite
|
Sign up to set email alerts
|

Diapause termination of Rhagoletis cerasi pupae is regulated by local adaptation and phenotypic plasticity: escape in time through bet‐hedging strategies

Abstract: Persistence and thriving of univoltine, herbivore insect species of the temperate zone rely on obligate diapause response that ensures winter survival and synchronization with host phenology. We used a stenophagous fruit fly (Rhagoletis cerasi) with obligate pupae diapause to determine genetic and environmental effects on diapause intensity of geographically isolated populations with habitat heterogeneity. Pupae from two Greek and one German populations with various gene flow rates were exposed at five constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 80 publications
3
76
1
5
Order By: Relevance
“…In the fruit fl y Rhagoletis cerasi (Diptera: Tephritidae), both insuffi cient and extended exposure to chilling promote prolonged and facultative dormancy, respectively (Moraiti et al, 2014). In our experiment however, these factors can be ruled out as determinants of the prolonged diapause recorded for more than half of the pupae.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…In the fruit fl y Rhagoletis cerasi (Diptera: Tephritidae), both insuffi cient and extended exposure to chilling promote prolonged and facultative dormancy, respectively (Moraiti et al, 2014). In our experiment however, these factors can be ruled out as determinants of the prolonged diapause recorded for more than half of the pupae.…”
Section: Discussioncontrasting
confidence: 43%
“…In the case of T. ballus, the factors determining diapause termination remain un-known. Due to the high variability in diapause duration recorded among the pupae, despite being exposed to the same climatic conditions, temperature, photoperiod and/or humidity do not appear to be the cues triggering diapause termination, as reported for other species (Templado, 1981;Powell, 2001;Moraiti et al, 2014;Sakamoto et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, some differences were observed between temperature sums calculated from soil and air temperatures for 5% cumulative hatch and more so for duration of flight period. Different populations of R. cerasi pupae exposed to constant chilling temperatures in the range 0-12°C for different times overcome diapause in relation to adaptation of the local populations (Moraiti et al, 2014). Our study showed that 5°C and 7°C can be used as thermal thresholds for accumulation of degree days for the studied population, since no major differences were observed between the two thresholds.…”
Section: Discussionmentioning
confidence: 79%
“…Recent findings support the importance of DNA methylation in phenotypic plasticity in aphids. Moraiti et al 2014;Ogawa & Miura 2014;Mukherjee & Baudach 2016). There commonly are differences among genotypes within a species in their ability to phenotypically adjust to environmental changes, in other words there is often genetic variation for phenotypic plasticity (Görür et al , 2007.…”
Section: Introductionmentioning
confidence: 99%